Fungsi Badan Usaha Milik Desa (BUMDES) Sari Amertha Sudha Sidakarya dalam Meningkatkan Kesejahteraan Masyarakat Desa - Putu Gede Putra Dharma Yasa; Ida Ayu Putu Widiati; I Wayan Arthanaya (Fakultas Hukum, Universitas Warmadewa, 2021)
Bumdes is a new approach that aims to improve the welfare of the village community in exploring the potential that the village has. Bumdes is managed by the village and assisted by the village community. The problems that exist in this research; how is the management of bumdes based on Law no. 6 of 2014 concerning Villages, how is the effectiveness of Sari Amertha Sudha Sidakarya in improving community welfare. This research is an empirical research with a social approach. The management of BUMDes must be carried out using the principles of cooperation, involvement, emancipation, not being covered up, calculated and sustainable. In implementing BUMDes management, there are three things that must be considered, namely strengthening the management capacity of BUMDes, BUMDes financial reporting and administration, and developing business units. Therefore, the direction of BUMDes development policy focuses on efforts to facilitate human resource development, strengthening institutions, increasing access to capital, and advocating for policies formulated based on priority scales. The effectiveness of bumdes Sari Amertha Sudha in an effort to improve the welfare of the village community through economic development. The form of community participation to participate in the development of BUMDes is to participate in planning, participate in efforts to manage bumdes and participate in monitoring and evaluating bumdes Sari Amertha Sudha Sidakarya.